The role of glucose metabolism in cardiac remodeling induced by tobacco smoke exposure - Azevedo, Paula S. [UNESP]; Ferreira, Vanessa C. M. P. [UNESP]; Santos, Priscila [UNESP]; Gonçalves, Andréa de Freitas [UNESP]; Okoshi, Marina P. [UNESP]; Fernandes, Ana Angelica Henrique [UNESP]; Roscani, Meliza Goi [UNESP]; Polegato, Bertha F. [UNESP]; Paiva, Sergio [UNESP]; Zornoff, Leonardo A. M. [UNESP]; Minicucci, M. [UNESP] (My University, 2015)
Therefore The aim of this study is to investigate the cardiac glucose metabolism pathways in cardiac remodeling induced by TS. Methods 20 animals were allocated into 2 groups: group of animals exposed to tobacco smoke (TS) and group animals not exposed to cigarette smoke (C). After 2 months the animals were subjected to: a) echocardiographic study; e) spectrophotometric evaluation of energy metabolism enzymes and f) Western blot for Akt and AMPK.The TS group showed larger left atrium size and lower ejection fraction than those of group. The animals showed the same body weight (p = 0.3), heart rate ( p = 0.4) and mean arterial pressure. As regards the analysis of energy metabolism enzymes, phosphofructokinase (PFK) (C 138 ± 24, TS=198 ± 31, p = 0.003), LDH (C =121 ± 31, TS= 167 ± 27, p = 0.017) and pyruvate dehydrogenase (PDH) (C=208 ± 18, TS= 211 ± 27, p=0,83) were greater in the TS group and citrate synthase (C =39,0 ±2.32, 25.53 ± TS=5.36, p <0.001), complex I (C =5.03 ± 0.48, TS=2.75 ± 0.62, p <0.001), complex II (C=5.32 ± 0.93; TS= 2.48 ± 0.78, p <0.001) , ATP synthase (C=57.91 ± 7.24, TS= 21.18 ± 4.84 p <0.001) were lower in the TS group. Akt/Aktp was similar between the groups. AMPK was reduced in CS group (p<0,001).Conclusion: During early cardiac remodeling, there is an increase in glucose metabolism. In this study LDH and PFK , that represents glycolytic pathways were increased. However, the citric acid cicle and mitochondrial respiratory chain may be compromised. One of the key modulators of these features may be AMPK.